In Vitro Anti-Inflammatory Activity in Arthritic Synoviocytes of A. brachypoda Root Extracts and Its Unusual Dimeric Flavonoids - Salgado, Carlota; Morin, Hugo; Coriolano de Aquino, Nayara; Neff, Laurence; Quintino da Rocha, Cláudia; Vilegas, Wagner [UNESP]; Marcourt, Laurence; Wolfender, Jean-Luc; Jordan, Olivier; Ferreira Queiroz, Emerson; Allémann, Eric (MDPI, 2020)
Arrabidaea brachypoda is a plant commonly used for the treatment of kidney stones, arthritis and pain in traditional Brazilian medicine. Different in vitro and in vivo activities, ranging from antinociceptive to anti-Trypanosoma cruzi, have been reported for the dichloromethane root extract of Arrabidaea brachypoda (DCMAB) and isolated compounds. This work aimed to assess the in vitro anti-inflammatory activity in arthritic synoviocytes of the DCMAB, the hydroethanolic extract (HEAB) and three dimeric flavonoids isolated from the DCMAB. These compounds, brachydin A (1), B (2) and C (3), were isolated both by medium pressure liquid and high-speed counter current chromatography. Their quantification was performed by mass spectrometry on both DCMAB and HEAB. IL-1β activated human fibroblast-like synoviocytes were incubated with both extracts and isolated compounds to determine the levels of pro-inflammatory cytokine IL-6 by enzyme-linked immunosorbent assay (ELISA). DCMAB inhibited 30% of IL-6 release at 25 µg/mL, when compared with controls while HEAB was inactive. IC50 values determined for 2 and 3 were 3-fold higher than 1. The DCMAB activity seems to be linked to higher proportions of compounds 2 and 3 in this extract. These observations could thus explain the traditional use of A. brachypoda roots in the treatment of osteoarthritis.
Keywords: anti-inflammatory activity; Arrabidaea brachypoda; flavonoids; high-speed counter current chromatography; mass-spectrometric quantification; osteoarthritis